The biomass characteristics of \(Hydropuntia eucheumatoides\) (Harvey) in the tidal beach of Hon Rua Island, Nha Trang Bay: potential source for exploitation, culture, and food processing - Thanh Trung, Vo; Mai Duc, Tran; Thi Mo, Vu; Xuan Cuong, Dang; Trong Nghia, Le; Van Huynh, Tran (Academia Journal of Biology, 2022)
The study of biomass characteristics of Hydropuntia eucheumatoides (Harvey) (local name in Vietnam, Rong Cau chan vit) in Hon Rua - Nha Trang bay is a comprehensive study of its resources. The results of the study have described in detail the morphological characteristics, reproductive organs, weight and coverage of its in quadrat and habitats. As a result, other has successfully stored seaweed algae under laboratory condition for 30 days. The results can be shown that determined the appropriate harvesting time and direction to exploit and conserve resources and propagate this seaweed. In addition, the main chemical and carbohydrate components of this seaweed have also been identified which has shown great potential for their application in the processing of high value food and medicine products in Vietnam in the future.